Biological maturation, morphology, fitness, and motor coordination as part of a selection strategy in the search for international youth soccer players (age 15-16 years) - Vandendriessche, J. B.; Vaeyens, R.; Vandorpe, B.; Lenoir, M.; Lefevre, J.; Philippaerts, R. M. (Journal of Sports Sciences, 2012)
We report the morphology (height, weight, body fat, body mass index), fitness (strength, speed, agility, flexibility), and soccer-specific (dribbling) and non-specific motor coordination skills (Körper KoordinationsTest für Kinder; KTK) of 78 Belgian international youth soccer players aged 15?16 years with varying biological maturity status. The more mature players (U16 and U17) possessed higher morphological measures and outperformed their later maturing peers (U16 Futures and U17 Futures) on almost all fitness tests. However, soccer-specific and non-specific motor coordination tests did not distinguish the more mature players from the later maturing players in both age groups. When adjusted for the confounder (age at peak height velocity), multivariate analysis of covariance revealed that several morphology- and fitness-related parameters did not differ between selection groups, again in both age groups. These findings indicate that biological maturation affects morphology and fitness more so than motor coordination skills. In conclusion, to prevent the dropout of promising late maturing players, we suggest avoiding one-dimensional approaches and to include measures of biological maturity status as well as maturity independent performance tests during the talent identification and selection process.